Prevalence and genotype distribution of hdv virus among chronic hepatitis b carriers in Hospital Universiti Sains Malaysia - Hadi, Fathin (2023)
Background HDV is one of the viral Hepatitis variants caused by the Hepatitis Delta virus. The HDV virus is unique in that it requires Hepatitis B for its propagation. HDV infection can present as co-infection (both Hepatitis B and D co-occur) or superinfection (subsequent infection with HDV after being infected with Hepatitis B). The combination of both Hepatitis B and D can lead to a severe form of chronic viral hepatitis as it can cause rapid liver cell injury and death, and may lead to the formation of hepatocellular carcinoma. HDV virus genotypes are known to be geographically distributed globally, with HDV 1 as the most frequently found genotype in high-income countries such as America and among European countries. In contrast, HDV 3, more commonly seen in South America, is more aggressive and may cause fulminant hepatitis. HDV 2 is commonly found in Asia. Due to the successful global Hepatitis B virus vaccination program, the number of HDV infections is declining worldwide. HDV infection can be prevented by Hepatitis B immunisation, but treatment success rates are low. Methodology This study was a non-interventional, cross-sectional cohort study. Participants who fulfilled the inclusion criteria and exclusion criteria were recruited from Hospital Universiti Sains Malaysia from 1st February 2020 till 27th January 2023. Selected clinical parameters were obtained with one-off blood taking for further analysis. HBV DNA extracted from serum was used for genotyping for HBV by using established specific primers in a two-tail PCR. Direct sequencing methods were used for the HBV genotypes detection, representing the eight HBV genotypes A to G, was performed using the MEGA 5 software. HDV-RNA detection uses RT PCR protocol using a specialised HDV nested primer to detect and amplify HDV. The PCR product will further be used for HDV genotyping according to the RFLP profile. Eight prototype HDV-genotype sequences were retrieved from the NCBI Gene bank for alignment and HDV genotyping. Results A total of 226 HBV positive subjects were recruited in the study. 26 subjects were HDV-positive from the HDV ELISA test. A total of 2 HDV genotypes were identified, which were genotype 1 with 9 subjects (34.6%) and genotype 2 with 4 subjects (15.4%). A total 13 subjects (50%) were unable to determine the HDV genotypes. From these 26 subjects, five subtypes of Hepatitis B were found 9 (34.6%) subtype B1, 5 (19.2%) subtype B2, 7 (26.9%) subtype B3, 4 (15.4%) subtype B4 and 1 (3.8%) subtype B5. From this study, no clinical association was found between the presence of liver cirrhosis with specific HDV genotypes with a p-value of 0.127 (p-value >0.05). In addition, this study found no association between AST and ALT levels with specific HDV genotypes with a p value of 0.821 (p-value >0.05). From our research, we could not demonstrate any significant association between HDV genotypes and specific selected clinical parameters. Conclusion From 226 total subjects, 26 subjects were positive HDV ELISA test. A total of 5 Hepatitis B subtypes were found with the most prevalent genotype of Hepatitis B; Hepatitis B Subtype B1 with 9 (34.6%) subjects, Hepatitis B Subtype B2 with 5 (19.2%) subjects, Hepatitis B Subtype B3 with 7 (26.9%) subjects, Hepatitis B Subtype B4 with 4 (15.4%) subjects, and Hepatitis B Subtype B5 with 1 (3.8%) subject. The data showed that genotype 1 is the most prevalent HDV genotype, with 9 subjects (34.6%), followed by genotype 2 with 4 (15.4%). We could not identify the HDV genotype sequences for 13 subjects (50%) due to several factors while handling the specimens like the small concentration of the synthesized cDNA from the RNA extraction, the volatility of RNA, and the unstable nature of RNA, the later usually cause loss of RNA integrity causes cDNA to denature early and in some cases produce non readable amplicons during its amplification using nested PCR. There was no significant association found between the HDV genotypes with the clinical manifestation.